CROSS-SECTIONAL STUDY IDENTIFYING THE PREVALENCE OF SLEEP DISTURBANCES AND ASSOCIATED RISK FACTORS IN MEDICAL STUDENTS: Prevalence of sleep disturbances - Djordjevic, Sofija; Jovanović, Aleksa; Nikolić, Vladimir; Pekmezovic, prof. dr Tatjana (Medical Research, 2025)
Disturbances in sleep can lead to poor academic and health outcomes. There is a gap in the current literature on prevalence of sleep disturbances, and their influence on a variety of associated factors. Our study seeks to understand the prevalence of sleep disturbances, and the effects it has on a medical students. A cross-sectional survey was conducted at the University of Belgrade, Faculty of Medicine between April and September of 2023. A sample of 70 medical students provided answers to a novel questionnaire, the BDI, and the PSQI, to evaluate lifestyle habits and demographics, depressive symptoms, and sleep quality. Univariate linear regression determined that chronic diseases, feeling of stress in the past 12 months, sleep duration, difficulty falling or staying asleep, consumption of sleep pills, and BDI score were strong predictors for the PSQI global score. Multivariate linear regression analysis showed that chronic diseases and depression were the most influential factors on participants’ sleep quality. Sleep quality in students is heavily influenced by chronic diseases and depressive symptoms, making it necessary to prevent these symptoms.